Inclusive Leadership, Trustworthiness, and Trust in Leaders on Organizational Citizenship Behaviour - Zamzami Sabiq; Amiartuti Kusmaningtyas; Sumiati (Jurnal Manajemen Bisnis, 2026)
This study aims to prove and analyze the influence of Inclusive Leadership and Trustworthiness on Organizational Citizenship Behaviour (OCB) with Trust in Leaders as a mediating variable among employees of the Scout Movement Quarters (Kwartir Gerakan Pramuka) throughout East Java. This research employs a quantitative approach with a causal explanatory design. The population in this study comprises 144 employees of the Scout Movement Quarters throughout East Java. The sampling technique utilized was total sampling (census method), resulting in a sample of 144 respondents. Data collection was conducted using Google Forms and measured using a Likert scale. The data analysis technique utilized Structural Equation Modeling (SEM), processed using Partial Least Square (PLS) software and SPSS version 26. The results indicate that: 1) Inclusive Leadership has a significant effect on Trust in Leaders; 2) Trustworthiness has a significant effect on Trust in Leaders; 3) Trust in Leaders has a significant effect on Organizational Citizenship Behaviour (OCB); 4) Trust in Leaders significantly mediates the effect of Inclusive Leadership on Organizational Citizenship Behaviour (OCB); and 5) Trust in Leaders significantly mediates the effect of Trustworthiness on Organizational Citizenship Behaviour (OCB).